2022
DOI: 10.1093/oso/9780192848925.001.0001
|View full text |Cite
|
Sign up to set email alerts
|

Research Methods in Deliberative Democracy

Abstract: Research Methods in Deliberative Democracy is the first book that brings together a wide range of methods used in the study of deliberative democracy. It offers thirty-one different methods that scholars use for theorizing, measuring, exploring, or applying deliberative democracy. Each chapter presents one method by explaining its utility in deliberative democracy research and providing guidance on its application by drawing on examples from previous studies. The book hopes to inspire scholars to undertake met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 387 publications
0
2
0
1
Order By: Relevance
“…Recentemente, estudiosos do campo democrático deliberativo têm indicado uma ampla diversidade de técnicas de pesquisas, utilizadas de modo combinado, o que expressa um amplo pluralismo metodológico (Ercan et al, 2022). Destacam-se, por exemplo, um variado conjunto de contribuições realizadas no âmbito dos fóruns deliberativos.…”
Section: Subsistemas Deliberativos E O Problema Dos Seus Conectores E...unclassified
“…Recentemente, estudiosos do campo democrático deliberativo têm indicado uma ampla diversidade de técnicas de pesquisas, utilizadas de modo combinado, o que expressa um amplo pluralismo metodológico (Ercan et al, 2022). Destacam-se, por exemplo, um variado conjunto de contribuições realizadas no âmbito dos fóruns deliberativos.…”
Section: Subsistemas Deliberativos E O Problema Dos Seus Conectores E...unclassified
“…To promote democratic deliberation even further, research methods can expand beyond the limited scope of surveys, instead facilitating conversations and dynamic exchanges via deliberative methods (Ercan et al, 2022). Asking participants to consider complex policy problems in a survey limits their ability to understand the discourse's broader context.…”
Section: Facilitating and Catalysing Democratic Participationmentioning
confidence: 99%
“…Various psychological studies have demonstrated that the relevant concepts of perceived effectiveness (Cojuharenco et al, 2016), participative efficacy (Bamberg et al, 2015;Hamann & Reese, 2020;van Zomeren et al, 2013), and sense of control (Eom et al, 2018) are important determinants of environmental collective actions and policy support. What's more, direct involvement in democratic processes such as policy recommendations can mitigate the extractive logic of social science and survey research (Ercan et al, 2022;Reinharz & Davidman, 1992). The rich output of data from deliberative research on the public acceptability of policies can form a social mandate to provoke governments' policy planning (Howarth et al, 2020), further reinforcing the consequentiality of such research agendas.…”
Section: Facilitating and Catalysing Democratic Participationmentioning
confidence: 99%